Clinical experience in treatment of diffuse unilateral subretinal neuroretinitis - Relhan N (Dove Medical Press, 2015)
Nidhi Relhan,1,2 Avinash Pathengay,2,3 Vishal Raval,2 Sameera Nayak,2 Himadri Choudhury,3 Harry W Flynn Jr11Department of Ophthalmology, Bascom Palmer Eye Institute, University of Miami Miller School of Medicine, Miami, FL, USA; 2Kode Venkatadri Chowdry Campus, Vijayawada, Andhra Pradesh, India; 3Retina and Uveitis Services, LV Prasad Eye Institute, GMR Varalakshmi Campus, Visakhapatnam, Andhra Pradesh, India Purpose: To describe the clinical features, management, and outcomes of patients with diffuse unilateral subacute neuroretinitis (DUSN). Methods: A noncomparative, consecutive analysis of case series from two tertiary care campuses of LV Prasad Eye Institute, India, between January 2011 and April 2014 was performed. Medical records of the patients presenting with DUSN (early or late stage) were reviewed. Results: The current study included 13 patients. The majority (10/13, 76.92%) of the patients were aged 20 years or less. All patients had unilateral eye involvement. Visual acuity at presentation was 20/200 or worse in 9/13 (69.23%) patients. A delay in diagnosis occurred in 6/13 patients, and initial diagnosis in these patients included retinitis pigmentosa (4 patients) and posterior uveitis (2 patients). Clinical features included early presentation (prominent vitritis, localized retinitis, and vasculitis) in 7/13 (53.85%) patients and late presentation (attenuation of vessels, retinal pigment epithelium atrophic changes, and optic atrophy) in 6/13 (46.15%) patients. Worm could not be identified in any of the cases. All the patients received laser photocoagulation of retina and oral albendazole treatment for a period of 30 days. With treatment, visual acuity improved in seven patients (six early stage, one late stage) and remained unchanged in six patients. Mean follow-up period was 8.69 months (range, 1–21 months). The mean central foveal thickness in the affected eye, done by optical coherence tomography, during the late stage of the disease was 188.20±40 µm (range, 111–242 µm), which was significantly thinner than the fellow eye, 238.70±36.90 µm (range, 186–319 µm), P=0.008. Conclusion: DUSN is a serious vision threatening disease, which may progress to profound vision loss in the later stage of the disease. Visualization of subretinal worm is usually not possible. Treatment with high-dose albendazole therapy and laser photocoagulation may alter the blood–retinal barrier and may be useful in achieving visual recovery. Keywords: diffuse unilateral subacute neuroretinitis, retinitis pigmentosa, OCT, albendazole therapy, central macular thickness